DNA Metabarcoding Revealed Interspecific Dietary Difference and Prey Selectivity in Juvenile Horseshoe Crabs Carcinoscorpius rotundicauda and Tachypleus tridentatus From Hong Kong - Lee, Bo Yee; Wakabayashi, Kaori; Sin, Simon Yung Wa; Ohtsuka, Susumu; Tsang, Ling Ming (Frontiers in Marine Science, 2021)
Horseshoe crabs provide important ecological services including bioturbation and linking of food web in the shallow waters, but their populations are declining globally, leading to major concerns on conservation of these iconic animals. Baseline information of horseshoe crab ecology, such as their trophic role and food source, is pre-requisite for habitat protection plan and captive restocking program. Trophic ecology of Asian horseshoe crabs is relatively poorly understood and previous studies on their juveniles have suggested that they are selective feeders rather than opportunistic generalists. This study demonstrates a non-invasive approach, using DNA metabarcoding analyses of the nuclear 18S rRNA gene on fecal samples to assess the dietary compositions of Carcinoscorpius rotundicauda and Tachypleus tridentatus juveniles to (1) determine their dietary compositions and trophic roles in their ecosystem, (2) determine any prey selectivity, and (3) distinguish the interspecific dietary differences with potential implications on the habitat requirement and ecological partitioning between these two horseshoe crab species. The results based on relative read abundance (RRA) suggested that oligochaetes were the major prey items for both C. rotundicauda (41.6%) and T. tridentatus (32.4%). Bivalves and crustaceans were second major prey groups for C. rotundicauda (8.6 and 8.4%, respectively). Surprisingly, anthozoans contributed a considerable portion of T. tridentatus’s diet (22.8%), which has never been reported. Furthermore, the major prey groups identified in the fecal samples were not the dominant benthic organisms in the studied area as revealed by environmental DNA (eDNA) analyses on the sediment samples, implying that both species are selective feeders rather than dietary generalists. Significant differences observed in the dietary compositions of the two species might be partially due to the difference in habitat preference between the two species. This study provides new insights into the trophic ecology of the two Asian horseshoe crab species in the estuarine habitat and establishes a new framework for future detailed molecular dietary analyses on all developmental stages of horseshoe crabs around the world, which will allow us to evaluate the food sources needed for the survival of horseshoe crabs and facilitate future conservation strategies without killing the animals.